The Status of the Noble Prophetic Hadith in Islamic Law - Oglah, Kawther Ahmed (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2025)
The Noble Prophetic Hadith holds a pivotal role as a primary source in Islamic legal theory, complementing the Qur’an in shaping jurisprudence and ethical frameworks for Muslim societies. Despite its foundational position, contemporary legal discourse faces challenges regarding authenticity, contextual interpretation, and its adaptability to modern legal issues. These concerns necessitate a comprehensive reassessment of the Hadith’s status and application in Islamic law. The primary objective of this study is to analyze the multifaceted functions of Hadith within the Sharia framework, focusing on its role in interpreting the Qur’an, formulating legal maxims, and guiding judicial reasoning across diverse Islamic schools of thought. Employing a qualitative method grounded in library research, the study conducts an analytical review of classical juristic methodologies alongside modern scholarly perspectives. Primary and secondary sources, including Hadith compilations, works of usul al-fiqh, and contemporary legal literature, are critically examined to trace historical developments and current debates. The findings reveal that the Hadith has maintained its dynamic relevance by continuously informing legal reasoning and ethical principles despite modern challenges of contextualization and reinterpretation. While authenticity remains a central concern, evolving methodologies in Hadith criticism and legal theory have strengthened its authority in addressing contemporary issues. This study contributes to the discourse by reaffirming the enduring significance of the Prophetic tradition as an indispensable pillar of Islamic jurisprudence. It underscores the necessity of integrative approaches that harmonize classical principles with present-day realities, ensuring the continued vitality of Hadith in shaping legal and moral norms.